Liquid Chromatography/Electrospray Ionisation Tandem Mass Spectrometric Study of Sitagliptin and its Stressed Degradation Products - Vishnuvardhan, C.; Radhakrishnanand, P.; Navalgund, S. G.; Satheeshkumar, N. (Drug Research, 2014)
A sensitive UPLC positive ion electrospray tandem mass spectrometry method was developed and validated for identification of degradation products of sitagliptin formed during stress study. Six of the major degradants were identified with the proposed method. The separation of sitagliptin and its degradation products was achieved on a Acquity BEH C-18 column (50×2.1 mm, 1.7 µm) using a gradient programme. The mobile phase consists of solvent A (10 mM ammonium formate, pH 6.4 adjusted with formic acid) and solvent B (acetonitrile) and quantitative evaluation was performed at 267 nm with a flow rate of 0.15 mL min−1. Suitability of this method for the quantitative determination of the drugs was proved by validation in accordance with International Conference on Harmonization (ICH) guidelines and can be used for routine analysis of sitagliptin formulations in quality control.
Keywords: anti-diabetic drug; sitagliptin; UPLC/MS